Kedudukan Hukum Leasing Kredit Kendaraan Bermotor Penyelesaian Wanprestasi dengan cara BPSK dan melalui Leasing - Pardamean Harahap (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research discusses the legal position of motor vehicle credit leasing, especially regarding the resolution of defaults in leasing agreements through the BPSK institution and the dispute resolution mechanism through the leasing channel itself. Motor vehicle leasing agreements often experience default due to the debtor's inability to fulfill installment payment obligations. This research aims to examine the legal position of leasing agreements in relation to default and analyze the dispute resolution mechanism through BPSK. This research uses a normative juridical approach with descriptive analysis. The research results show that leasing agreements have a clear legal basis, even though they are not explicitly regulated in the Civil Code. Default dispute resolution can be done through mediation, conciliation or arbitration at BPSK. Dispute resolution through BPSK provides space for consumers and business actors to reach an agreement without going through a more formal litigation process.